An in-depth Analysis of the Degree of Implementation of Integrated Care for Diabetes in Primary Health Care in Cambodia - Vannarath Te; Sereyraksmey Long; Wim Van Damme; Por Ir; Edwin Wouters; Josefien van Olmen (International Journal of Integrated Care)
Introduction: With the rising prevalence of type 2 diabetes (T2D), three care initiatives for T2D are being scaled-up in Cambodia to improve availability and accessibility of integrated care for T2D: (1) hospital-based care, (2) health centre-based care, and (3) community-based care. This case study aims to share learnings from an in-depth analysis of the level of integrated care implementation in these care initiatives for T2D in Cambodia. Description: Twenty public health facilities in five operational districts were assessed on six integrated care components: (1) early detection and diagnosis, (2) treatment in primary care services, (3) health education, (4) self-management support, (5) structured collaboration, and (6) organisation of care. Two raters independently scored each facility on a 0–5 scale based on multiple sources of data and reached a consensus. Discussion: The in-depth analysis showed that the three care initiatives were not implemented in an integrated manner, with low implementation scores (1 or 2 out of 5) in all selected settings. The presence of health centre-based care was associated with higher scores for early detection and diagnosis and treatment in primary care services, while the presence of community-based care was related to structured collaboration and organisation of care. Conclusion: The evidence suggests that while each care initiative has its potential contributions towards integrated care for T2D, the three care initiatives should be effectively implemented in an integrated manner in order to potentially produce the desired outcomes.